Prove the following:
$ (\sqrt{3}+1)\left(3-\cot 30^{\circ}\right)=\tan ^{3} 60^{\circ}-2 \sin 60^{\circ} $

AcademicMathematicsNCERTClass 10

To do:

We have to prove that \( (\sqrt{3}+1)(3-\cot 30^{\circ})=\tan^{3} 60^{\circ}-2\sin 60^{\circ} \).

Solution:  

We know that,

$\cot 30^{\circ}=\sqrt3$

$\tan 60^{\circ}=\sqrt3$

$\sin 60^{\circ}=\frac{\sqrt3}{2}$

Let us consider LHS,

$(\sqrt{3}+1)(3-\cot 30^{\circ})=(\sqrt{3}+1)(3-\sqrt3)$

$=(\sqrt{3})(3)-(\sqrt3)^2+1(3)-1(\sqrt3)$

$=3\sqrt3-3+3-\sqrt3$

$=2\sqrt3$     

Let us consider RHS,

$\tan^{3} 60^{\circ}-2\sin 60^{\circ}=(\sqrt3)^3-2(\frac{\sqrt3}{2})$

$=3\sqrt3-\sqrt3$

$=2\sqrt3$

LHS $=$ RHS

Hence proved.

raja
Updated on 10-Oct-2022 13:29:22

Advertisements